VARIABILIDADE ORÇAMENTÁRIA COM DIFERENTES BASES DE COMPOSIÇÕES UNITÁRIAS: ESTUDO DE CASO DE DOIS PRÉDIOS RESIDENCIAIS EM BELÉM/PA - Santos, Jéssica; Ferreira, Luciana; Maues, Luiz; Duarte, Andre; Carvalho, Andre (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Linked to a good management, the good development of a construction site is directly related to its budget cost. From this confirmation, the present work sought to analyze the variability of analytical budgets, carrying out a case study in two residential enterprises located in the city of Belém/PA, budgeting them in the same budget structure, but under different sources of composition (SINAPI and TCPO), which made it possible to compare the final and partial costs (by constructive steps) obtained from the one calculated by the company. It was found that the final values differed little among themselves, reaching a maximum variation of 6%, however, there are stages that showed significant differences between their costs, reaching 100% in some cases. It was concluded that the main causes of the price variations were due to the productivity indexes and inputs adopted in the databases. Therefore, the study showed that the technical and detailed analysis of the unitary compositions is of essential importance, since different compositions for the same services can directly influence the overall and per stage costs and, consequently, impact the viability, practicability and even the profit of what is desired in a civil work that is planned to be built.